A metric to measure long-term well-being of people living with HIV in Spain - María José Fuster-RuizdeApodaca; Trenton M. White; Carlos Prats-Silvestre; Francisco P. Holgado-Tello; Jeffrey V. Lazarus (BMC Medicine)
Abstract Background Achieving long-term well-being for people living with HIV (PLHIV) requires moving beyond viral suppression to address health-related quality of life (HRQoL), encompassing physical, mental, and social dimensions. This study aimed to develop a composite metric to monitor and improve the long-term well-being of PLHIV in Spain. Methods This study employs a Delphi consensus process with composite score analysis of cross-sectional survey data from 500 PLHIV in Spain. The Delphi method was employed to engage 43 experts to identify and prioritize indicators for three domains: comorbidity, discrimination, and quality of life. Data from validated instruments, including the Charlson Comorbidity Index and the WHOQOL-HIV-BREF tool, were used to construct a composite well-being score. Scores for each domain were weighted and standardized to create the long-term well-being index. Results The composite metric revealed that most participants had moderate well-being, with 70% scoring medium for comorbidities and 66% experiencing medium to high discrimination. About 15% reported poor quality of life, and nine participants exhibited the worst possible scores across all domains. The metric demonstrated the interrelated impact of comorbidity, discrimination, and quality of life on overall well-being. Conclusions This study introduces a long-term well-being composite metric that integrates comorbidity, discrimination, and HRQoL as critical domains for monitoring and improving the health of PLHIV. The metric provides a holistic, patient-centered framework to guide interventions and policy, supporting better outcomes for PLHIV in Spain and beyond.